2018
DOI: 10.1109/tifs.2018.2797000
|View full text |Cite
|
Sign up to set email alerts
|

Universal 3D Wearable Fingerprint Targets: Advancing Fingerprint Reader Evaluations

Abstract: We present the design and manufacturing of high fidelity universal 3D fingerprint targets, which can be imaged on a variety of fingerprint sensing technologies, namely capacitive, contact-optical, and contactless-optical. Universal 3D fingerprint targets enable, for the first time, not only a repeatable and controlled evaluation of fingerprint readers, but also the ability to conduct fingerprint reader interoperability studies. Fingerprint reader interoperability refers to how robust fingerprint recognition sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Coefficients ci are calculated by minimizing the discrepancy (9) and (10). As basic deformations, it is suggested to use the "principal" deformations obtained by the main component method on the reference fingerprint array [21,22]. To calculate the main components, three FVC2002 databases were used, containing images from optical and capacitive fingerprint scanners [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Coefficients ci are calculated by minimizing the discrepancy (9) and (10). As basic deformations, it is suggested to use the "principal" deformations obtained by the main component method on the reference fingerprint array [21,22]. To calculate the main components, three FVC2002 databases were used, containing images from optical and capacitive fingerprint scanners [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Engelsma et al [17] suggested how fingerprint can be enhancing in future to avoid image variation results from fingerprint captures. They presented a universal 3d fingerprint target as an alternative to improve images variations.…”
Section: 1fingerprint Biometric Authenticationmentioning
confidence: 99%
“…However, the matching performance is still quite high considering the stringent operating point (FAR = 0.1%). Furthermore, studies have shown that when different fingerprint readers are used for enrollment and subsequent verification or identification, the matching performance indeed drops [49], [50], [51]. Finally, we are currently investigating other approaches for processing and downsampling RaspiReader images to reduce some of the drop in crossreader performance.…”
Section: Interoperability Of Raspireadermentioning
confidence: 99%